Effects of 7-ketocholesterol on tamoxifen efficacy in breast carcinoma cell line models in vitro - Spalenkova, Alzbeta; Ehrlichova, Marie; Wei, Shouzou; Peter Guengerich, F; Soucek, Pavel (The Journal of steroid biochemistry and molecular biology, 2023)
Oxysterols play significant roles in many physiological and pathological processes including cancer. They modulate some of the cancer hallmarks pathways, influence the efficacy of anti-cancer drugs, and associate with patient survival. In this study, we aimed to analyze the role of 7-ketocholesterol (7-KC) in breast carcinoma cells and its potential modulation of the tamoxifen effect. 7-KC effects were studied in two estrogen receptor (ER)-positive (MCF-7 and T47D) and one ER-negative (BT-20) breast cancer cell lines. First, we tested the viability of cells in the presence of 7-KC. Next, we co-incubated cells with tamoxifen and sublethal concentrations of 7-KC. We also tested changes in caspase 3/7 activity, deregulation of the cell cycle, and changes in expression of selected genes/proteins in the presence of tamoxifen, 7-KC, or their combination. Finally, we analyzed the effect of 7-KC on cellular migration and invasion. We found that the presence of 7-KC slightly decreases the efficacy of tamoxifen in MCF-7 cells, while an increased effect of tamoxifen and higher caspase 3/7 activity was observed in the BT-20 cell line. In the T47D cell line, we did not find any modulation of tamoxifen efficacy by the presence of 7-KC. Expression analysis showed the deregulation in CYP1A1 and CYP1B1 with the opposite trend in MCF-7 and BT-20 cells. Moreover, 7-KC increased cellular migration and invasion potential regardless of the ER status. This study shows that 7-KC can modulate tamoxifen efficacy as well as cellular migration and invasion, making 7-KC a promising candidate for future studies.
Keywords: MCF-7 Cells; nádorové buněčné linie; Breast Neoplasms; tamoxifen; receptory pro estrogeny; kaspasa 3; 7-ketocholesterol; Cell Proliferation; Cell Line, Tumor; MFC-7 buňky; Breast cancer; chemorezistence; ženské pohlaví; Humans; Caspase 3; Receptors, Estrogen; Drug Resistance, Neoplasm; Migration; Proliferation; Tamoxifen; Antineoplastic Agents, Hormonal; nádory prsu; proliferace buněk; Female; lidé; hormonální protinádorové látky